Environmental effects of foreign direct investment in India: pollution haven or pollution halo? - Holtbrügge, Dirk; Raghavan, Nikhila (Critical Perspectives on International Business, 2025)
Purpose: There is controversy over whether foreign direct investment (FDI) increases or reduces environmental degradation in host countries resulting in pollution havens or pollution halos. Based on the concept of scale, technology and composition effects, this paper aims to examine the causal relationship between FDI and carbon dioxide (CO2) emissions in India. Design/methodology/approach: This paper analyzes panel data of the three most polluting industries between 2005 and 2021 by conducting a Granger causality test. Findings: The results provide evidence of pollution havens in the manufacturing and transportation industry, and in the metallurgy and chemical sectors within the manufacturing industry. Research limitations/implications: FDI inflows and CO2 emissions are characterized by large regional variations in India. Hence, future studies of the pollution haven vs pollution halo effect in India could therefore use state-level or even district-level data to test for regional variations. Practical implications: This paper provides policy recommendations such as increasing the absorptive capacity of local firms to strengthen the technique effect, which would help India combat climate change. Social implications: Increasing the absorptive capacity of local firms through incentives such as subsidies and environmental requirements in public contracts can lead to job creation in the green technology sector. This can provide new employment opportunities, especially in R&D and sustainable technology fields, boosting the local economy. Originality/value: The study adds to the understanding of the endogenous relationship between FDI and environmental degradation, the importance of lagged feedback responses and the impact of industry- and sector-specific influences on this relationship.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Foreign direct investment policy; Granger causality; International trade; Pollution halo hypothesis; Pollution haven hypothesis

The Internationalization Strategy of NürnbergMesse: Advantages of a Late Follower - Altendorf, Franziska; Raghavan, Nikhila; Holtbrügge, Dirk (The Internationalization of Firms. Case Studies from the Nürnberg Metropolitan Region, 2024)
CRIS-Team Scopus Importer:2025-02-04